Teknologi dan Personalisasi Pembelajaran Pendidikan Islam untuk Generasi Z - Yusuf, Budi (Journal of Instructional and Development Researches, 2024)
This study discusses the integration of technology and personalized learning in Islamic education for Generation Z. The research employs a qualitative approach with literature review as the main method. The findings indicate that technology can enhance learning effectiveness by providing interactive tools and platforms accessible anytime and anywhere. Technology allows for more engaging material delivery and helps students understand Islamic concepts through visualization and simulation. Personalized learning allows curriculum and teaching methods to be tailored to individual student needs, which can increase their motivation and learning outcomes. Generation Z, who have grown up in a digital environment, greatly benefit from this approach. However, challenges such as the digital divide, negative impacts of technology on social and spiritual interactions, and the substantial resources required for personalized learning need to be addressed. A balanced strategy between the use of technology and the preservation of Islamic values is necessary to ensure that Islamic education remains relevant and effective in the digital era. Developing technological infrastructure, training programs for teachers and students, and relevant curricula are essential to achieving these goals.